Representasi Pribumi dalam Iklan Surat Kabar Pandji Poestaka 1940-1941 - Noveri Faikar Urfan (Jurnal Komunikasi, 2012)
Pandji Poestaka is a newspaper founded by the Netherland Indies colonial government, that is Commisie voor de Volkslectuur (Commission of the People Reading), or better known as Balai Poestaka. This study attempts to examine how the representation of natives in the colonial period in Pandji Poestaka ads 1940-1941. Using semiotics, this study shows that Pandji Poestaka ads has presented natives representation in the dichotomous class stratification. The native aristocracy (priyayi) and the underprivileged (wong cilik). Priyayi look represented the image of modernity: educated, wealthy, and civilized. Meanwhile, wong cilik has been overwritten by inferior image representation: traditional, blue-collar workers, and lazy. These representations, seen as part of the colonial strategy to maintain its position in the Netherland Indies. By representing social class among the natives, colonialism tried to keep the gap class. Colonialism also took advantage of the mass media (Pandji Poestaka) as an ideological state apparatus to continue, maintain power, and institutionalize the ideology of colonial rule.